2020
DOI: 10.1021/acs.energyfuels.0c01236
|View full text |Cite
|
Sign up to set email alerts
|

Role of 3D Alumina Foam Support on the Formation and Dispersion of Active NiMoS Phase for Hydrodesulfurization Application

Abstract: The role of 3D alumina foam support (Al-F) and titania-modified alumina foam support (Al-F-Ti-X, where X represents the weight ratio of Al-F/TiO 2 ) on the dispersion and catalytic activity of NiMo metals in the hydrodesulfurization (HDS) reaction of dibenzothiophene was studied in a batch reactor. The catalysts were characterized by X-ray diffraction (XRD), N 2 adsorption desorption isotherm, field emission scanning electron microscopy (FESEM), Fourier-transform infrared (FTIR) spectroscopy, temperature-progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…In recent years, sulfur oxides emitted from the combustion of sulfur-containing fossil fuels have caused serious damage to the environment; therefore, the production of ultraclean fuels is the development objective of petrochemical enterprises. Hydrodesulfurization (HDS) is commonly used to remove sulfur from fossil fuels, and improving the reactivity of catalysts is the key to this technology . It has been found that bimetallic catalysts containing Mo (or W) as the active metal and Co (or Ni) as the promoter have outstanding HDS activity .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, sulfur oxides emitted from the combustion of sulfur-containing fossil fuels have caused serious damage to the environment; therefore, the production of ultraclean fuels is the development objective of petrochemical enterprises. Hydrodesulfurization (HDS) is commonly used to remove sulfur from fossil fuels, and improving the reactivity of catalysts is the key to this technology . It has been found that bimetallic catalysts containing Mo (or W) as the active metal and Co (or Ni) as the promoter have outstanding HDS activity .…”
Section: Introductionmentioning
confidence: 99%
“…[88] Mostly, the choice of active metals is based on the level of hydrotreating operation with Ni(Co)Mo(W) being used as a conventional and most popular active metals over six decades in a carrier-free or supported matrix due to low cost and availability. [89][90][91][92][93][94] Moreover, the conventional active has may be employed as sulfided monometallic composed of Mo or W, bimetallic (NiMo, CoMo, NiW, CoW), trimetallic (NiCoMo, NiMoW, CoMoW, NiCoW) and ternary or multicomponent active metals. [95][96][97][98][99][100][101] In addition, various landmarks of noble and other transition metals have been reported.…”
Section: Active Phasementioning
confidence: 99%
“…HDS active metals are usually referred to the active phase after sulfidation in a stream of sulfur containing precursor, with a few exception to metal‐free carbon catalysts [88] . Mostly, the choice of active metals is based on the level of hydrotreating operation with Ni(Co)Mo(W) being used as a conventional and most popular active metals over six decades in a carrier‐free or supported matrix due to low cost and availability [89–94] . Moreover, the conventional active has may be employed as sulfided monometallic composed of Mo or W, bimetallic (NiMo, CoMo, NiW, CoW), trimetallic (NiCoMo, NiMoW, CoMoW, NiCoW) and ternary or multicomponent active metals [95–101] .…”
Section: Active Phasementioning
confidence: 99%
“…The recent strict environmental regulations limiting the level of sulfur in the transportation fuel has prompted the need to develop highly active and stable hydrodesulfurization (HDS) catalysts . Previous studies have shown a tremendous improvement in the catalyst activity through changing the active metals or addition of promoters to the active metal, synthesis route, and changing or modification of active metal supports. Textural and mechanical properties, high active metal dispersion, and low cost have made γ-Al 2 O 3 the most widely acceptable catalyst support for many industrial catalysts including the HDS catalyst . However, a big drawback of γ-Al 2 O 3 is that it shows strong metal–support interaction with active metals .…”
Section: Introductionmentioning
confidence: 99%